A new design of cryptographic hash function: gear - Alkandari, Abdulaziz M; Alkandari, Khalil Ibrahim; Taha Alshaikhli , Imad Fakhri; Alahmad, Mohammad A. (IIUM Press, 2015)

(untitled)
A hash function is any function that can be used to map data of arbitrary size to data of fixed size. A hash function usually has two main components: a permutation function or compression function and mode of operation. We will propose a new concrete novel design of a permutation based hash functions called Gear in this paper. It is a hash function based on block cipher in Davies-Meyer mode. It uses the patched version of Merkle-Damgård, i.e. the wide pipe construction as its mode of operation. Thus, the intermediate chaining value has at least twice larger length than the output hash. And the permutations functions used in Gear are inspired from the SHA-3 finalist Grøestl hash function which is originally inspired from Rijndael design (AES). There is a very strong confusion and diffusion in Gear as a result.